O30 Closure of perianal fistula in patients receiving ustekinumab in the SEAVUE and STARDUST trials. (19th June 2022) - Laurent, Peyrin-Biroulet; Panaccione, Remo; Gasink, Christopher; Hoops, Timothy; Izanec, James L; Ma, Tony; Nazar, Maciej; Bravata, Ivana; Lahaye, Marjolein; Irving, Peter M; Loftus, Edward; Danese, Silvio; et al.
Abstract : Introduction: Perianal fistulas are common and cause significant quality of life impairment in patients (pts) with Crohn's disease (CD). We report data on fistula closure from the SEAVUE and STARDUST studies. Methods: In SEAVUE, biologic-naïve pts with moderately-to-severely active CD were randomized to blinded UST (∽6 mg/kg IV at baseline then 90mg SC q8w) or adalimumab (ADA; 160/80 mg SC at baseline/W2, then 40mg SC q2w). In STARDUST, biologic-naïve+biologic-failure pts with moderately-to-severely active CD received open-label UST ∽6 mg/kg IV at baseline then 90mg SC at W8 and responders were randomized at W16 to maintenance treatment under standard-of-care (90mg SC q12w/q8w) or treat-to-target (90mg SC q12w/q8w with potential adjustment to q4w) regimens. The number of open and draining perianal fistulas was evaluated at baseline/end of maintenance (SEAVUE W52, STARDUST W48). Fistula resolution was defined as complete fistula closure. Results: In SEAVUE, 7 of 13 pts (53.8%) with active perianal fistulas at baseline in the UST group and 6 of 16 pts (37.5%) in the ADA group had fistula resolution at W52. In STARDUST, 9 of 19 pts (47.4%) with active perianal fistulas at baseline had fistula resolution at W48 (fistula resolution, n=9 patients [q12w at W48: n=2, q8w: n=6 and q4w: n=1]; without fistula resolution, n=10 patients [q12w at W48: n=2, q8w: n=3, q4w: n=1 and discontinued before W48: n=4]). Among evaluable samples for PK analysis, fistula closure at W52/48 was not associated with higher serum drug concentrations at W16 or at end of maintenance ( Figure ). Results were consistent for UST in both studies and adalimumab in SEAVUE. Conclusion: Of pts with perianal fistulas at baseline in SEAVUE and STARDUST who received UST, 50% had fistula resolution after 1 year of maintenance treatment. There was no relationship between fistula resolution and serum drug concentrations, but no definite conclusions can be drawn given the small sample sizes. Abstract Topic: Inflammatory bowel disease Keywords: Perianal fistula, SEAVUE, STARDUST, Ustekinumab Disclosures: Laurent Peyrin-Biroulet reports personal fees from AbbVie, Allergan, Alma, Amgen, Applied Molecular Transport, Arena, Biogen, Boehringer Ingelheim, Bristol-Myers Squibb, Celgene, Celltrion, Enterome, Enthera, Ferring, Fresenius, Genentech, Gilead, Hikma, Index Pharmaceuticals, Janssen, Lilly, MSD, Mylan, Nestlé, Norgine, Oppilan Pharma, OSE Immunotherapeutics, Pfizer, Pharmacosmos, Roche, Samsung Bioepis, Sandoz, Sterna, Sublimity Therapeutics, Takeda, Tillots and Vifor; grants from AbbVie, MSD and Takeda; stock options from CTMA. Remo Panaccione has received consulting fees from AbbVie, Abbott, Alimentiv (formerly Robarts), Amgen, Arena, AstraZeneca, Bristol-Myers Squibb, Boehringer Ingelheim Celgene, Celltrion, Cosmos Pharmaceuticals, Eisai, Elan, Eli Lilly, Ferring, Galapagos, Genentech, Gilead Sciences, Glaxo-Smith Kline, Janssen, Merck, Mylan, Oppilan Pharma, Pandion Therapeutics, Pfizer, Progenity, Protagonist Therapeutics, Roche, Satisfai Health, Sandoz, Schering-Plough, Shire, Sublimity Therapeutics, Theravance, UCB, and Takeda; speaker fees from AbbVie, Arena, Celgene, Eli Lilly, Ferring, Gilead Sciences, Janssen, Merck, Pfizer, Roche, Sandoz, Shire, and Takeda; research/educational support from AbbVie, Ferring, Janssen, Pfizer, and Takeda; and has served on an advisory board for AbbVie, Amgen, Arena, , Bristol-Myers Squibb, Celgene, Celltrion, Eli Lilly, Ferring, Galapagos, Genentech, Gilead Sciences, Glaxo-Smith Kline, Janssen, Merck, Mylan, Oppilan Pharma, Pandion Pharma, Pfizer, Sandoz, Shire, Sublimity Therapeutics, Theravance, and Takeda. Christopher Gasink and James L. Izanec report employment with/funding by Janssen Scientific Affairs, LLC., a wholly owned subsidiary of Johnson & Johnson, and stock ownership in Johnson & Johnson. Tony Ma is a contract employee funded by Janssen Scientific Affairs. Timothy Hoops reports employment with/funding by Janssen Scientific Affairs, LLC., a wholly owned subsidiary of Johnson & Johnson, and stock ownership in Johnson & Johnson Maciej Nazar reports employment with/funding by Janssen-Cilag, Polska Sp. z o.o, a wholly owned subsidiary of Johnson & Johnson, and stock ownership in Johnson & Johnson. Ivana Bravata reports employment with/funding by Janssen-Cilag, Italy, a wholly owned subsidiary of Johnson & Johnson, and stock ownership in Johnson & Johnson. Marjolein Lahaye reports employment with/funding by Janssen-Cilag, B.V., Medical Affairs, a wholly owned subsidiary of Johnson & Johnson, and stock ownership in Johnson & Johnson. Peter M. Irving reports lecture fees from AbbVie, Celgene, Falk Pharma, Ferring, Janssen, MSD, Pfizer, Sapphire Medical, Sandoz, Shire, Takeda, Tillots, and Warner Chilcott; financial support for research from MSD, Pfizer, and Takeda; and advisory fees from AbbVie, Arena, Genentech, Gilead, Hospira, Janssen, Lilly, MSD, Pfizer, Pharmacosmos, Prometheus, Roche, Sandoz, Samsung Bioepis, Takeda, Topivert, VH2, Vifor Pharma, and Warner Chilcott. Edward V. Loftus, Jr. reports consulting fees from AbbVie, Amgen, Arena, Boehringer Ingelheim, Bristol Myers Squibb, Calibr, Celgene, Genentech, Gilead, Gossamer Bio, Iterative Scopes, Janssen, Lilly, Ono Pharma, Pfizer, Scipher Medicine, Sun Pharma, Takeda, and UCB and research support from AbbVie, Bristol Myers Squibb, Celgene, Genentech, Gilead, Gossamer Bio, Janssen, Pfizer, Receptos, Robarts Clinical Trials, Takeda, Theravance, and UCB. Silvio Danese consultancy fees from AbbVie, Alimentiv, Allergan, Amgen, AstraZeneca, Athos Therapeutics, Biogen, Boehringer Ingelheim, Celgene, Celltrion, Eli Lilly, Enthera, Ferring Pharmaceuticals Inc., Gilead, Hospira, Inotrem, Janssen, Johnson & Johnson, MSD, Mundipharma, Mylan, Pfizer, Roche, Sandoz, Sublimity Therapeutics, Takeda, TiGenix, UCB Inc. and Vifor; and reports lecture fees from AbbVie, Amgen, Ferring Pharmaceuticals Inc., Gilead, Janssen, Mylan, Pfizer and Takeda Bruce E. Sands discloses research grants from Takeda, Pfizer, Theravance Biopharma R&D, Janssen; consulting fees from 4D Pharma, Abivax, Abbvie, Alimentiv, Allergan, Amgen, Arena Pharmaceuticals, AstraZeneca, Bacainn Therapeutics, Boehringer-Ingelheim, Boston Pharmaceuticals, Bristol-Myers Squibb, Calibr, Capella Bioscience, Celgene, Celltrion Healthcare, ClostraBio, Enthera, F.Hoffmann-La Roche, Ferring, Galapagos, Gilead, Glaxo SmithKline, GossamerBio, Immunic, Index Pharmaceuticals, Innovation Pharmaceuticals, Ironwood Pharmaceuticals, Janssen, Kaleido, Kallyope, Lilly, MiroBio, Morphic Therapeutic, Oppilan Pharma, OSE Immunotherapeutics, Otsuka, Palatin Technologies, Pfizer, Progenity, Prometheus Biosciences, Prometheus Laboratories, Protagonist Therapeutics, Q32 Bio, Redhill Biopharma, Rheos Medicines, Salix Pharmaceuticals, Seres Therapeutics, Shire, Sienna Biopharmaceuticals, Sun Pharma, Surrozen, Takeda, Target PharmaSolutions, Teva Branded Pharmaceutical Products R&D, Thelium, Theravance Biopharma R&D, TLL Pharma, USWM Enterprises, Ventyx Biosciences, Viela Bio, Vivante Health, Vivelix Pharmaceuticals; and stock for Vivante Health and Ventyx Biosciences.